Priests and priestesses in Mycenaean Greece - Christina, Aamondt (2006)
The aim of this thesis is to investigate the evidence concerning the existence of a Mycenaean priesthood. The existence of religious specialists responsible for the performance of ritual acts is universal and can be attributed to their role as intermediaries between humans and the divine. Evidence from the Linear B tablets attest to the existence of priests (i-je-re-u) and priestesses (i-je-re-ja) during the high point of the Mycenaean period, responsible for mediating between the people and the divine in the performance of ritual acts. Textual and iconographic evidence indicate the performance of various cult practices, such as animal sacrifice and the celebration of festivals, complemented by archaeological evidence of cult installations and equipment employed. The fact that the majority of the evidence associates priests with the palatial centres indicates that they were closely connected to them, and that most likely the office of priesthood was restricted to the elite, even though the existence of priests in communities away from the palatial centres is not overlooked. Textual evidence provides information concerning the organisation of the priesthood, indicating that it was associated with a body of cult assistants, while a hierarchy existed among priests, most likely defined by the cult place they operated at and its connection with the palace. Finally, the examination of the association of cult places with economic matters in the Linear B tablets concludes that cult places had a certain degree of independence in terms of their maintenance and their cult needs.